State Security Vs Human Security: Which Should Prioritize The State or The Individual? - Anggayudha, Zaihan Harmaen; Rafsanjani, Jody Imam (Operations Research: International Conference Series, 2023)
Nowadays, the concept of human security is an issue that is often discussed, especially when issues regarding policies or how a country deals with the Covid-19 pandemic make headlines in every news report. The concept of human security shifts the focus point of security which previously focused on the state to become towards individuals. Often various discussions collide these two concepts under the pretext of finding the best way for the state to make an appropriate policy, especially during emergencies such as problems caused by the Covid-19 Pandemic. So to solve this problem it is necessary to re-understand the priorities in the security of a country in an emergency situation, especially in Indonesia. This paper aims to find out what is prioritized by the state in the event of an emergency. Literature study or desk research becomes a research method, accompanied by a conceptual and regulatory approach, then secondary data is analyzed descriptively. Based on the research, it was concluded that the concept of state security or human security should not be made as if they are contradictory but instead complement one another and become a thinking construct for the state to determine a priority in order to achieve common interests through an insecurity faced in an emergency situation. The state as the shelter of an individual certainly needs to be a top priority without neglecting the security of every individual in it. The difference in focus on the concept of state security and human security should not make both of them an option.